Codelivery of DOX and siRNA by folate-biotin-quaternized starch nanoparticles for promoting synergistic suppression of human lung cancer cells. (1st January 2019) - Li, Liangping; He, Suoju; Yu, Lizhen; Elshazly, Ezzat H; Wang, Hui; Chen, Kuanmin; Zhang, Song; Ke, Lixia; Gong, Renmin
Abstract: In this paper, the self-assembled folate-biotin-quaternized starch nanoparticles (FBqS NPs) were used as carrier system of doxorubicin (DOX) and siRNA IGF1R for the codelivery of both into human lung adenocarcinoma cell lines (A549 cells) in vitro. The cytotoxicity, targeted ligand competition, cell proliferation inhibition, cellular uptake, endocytosis mechanism and target protein suppression of drug-loaded FBqS NPs were evaluated in detail. Compared with several other drug formulations under same condition, siRNA IGF1R /DOX/FBqS NPs exhibited the greatest cytotoxicity to A549 cells and the cytotoxicity was competitively inhibited by free folate in dose-dependent manner. The A549 cells treated by siRNA IGF1R /DOX/FBqS NPs showed the lowest cell proliferation capacity. The energy-dependent clathrin- and caveolae-mediated endocytosis might be the primary cellular uptake mechanism of drug-loaded FBqS NPs. The expression of IGF1R protein in A549 cells treated by siRNA IGF1R /FBqS NPs declined dramatically. So the FBqS NPs were expected as the co-carrier system of chemotherapeutants and siRNAs for future clinical application.